Moderator effect over investors behavior lower preference towards mutual fund in Malaysia - Ch'ng, Sin Thong; Chew, Pei Xuan; Soh, Han Wei; Lean, Yan Sheng; Wong, Jie Kan (2020)
Mutual fund is an investment vehicle that pools money from investors to invest in investment products like stocks, bonds, money market instruments and other assets. The purpose of this study is to determine the factors that influence investors to have a low preference towards mutual fund with moderator effect, income level. By determining the relationship, the relationship between awareness, financial products, investment considerations and income level as the moderator towards investor intention. The data collection method used is a questionnaire survey with 416 respondents collected. Results are generated through Smart PLS 3.0. The findings of this study indicate that the model with moderator shows awareness, financial products and investment considerations has a positive relationship towards investor intention. In contrast, the model without a moderator, only awareness has a positive relationship towards investor intention, while financial products and investment considerations have shown a negative relationship towards investor intention.